Approach to Associationism in Sinaloa, México: 1875 a 1929 - López Alfaro, Gilberto (2024)
This work aims to demonstrate the existence of groups that gave way to the formation of civil society in the state of Sinaloa, Mexico. Through the critical-analytical method with a qualitative approach, we proceeded to review the bibliography, journalistic sources, and archives; with which it was possible to obtain the classification, division and segmentation in the fields: social, political and labor of these groups between the years of 1875 to 1939. These organizations were evidence of the transition from pre-modern society to a liberal, modern and revolutionary post in Sinaloa. The listed societies give us reference of the presence and the beginning of the political, charitable and social participation of women, as well as the creation of organizations in favor of the defense of labor rights. They also indicate the formalization of the political clubs that became the antecedents of the political parties.